Development Of Variable Valve Timing Mechanism For Compressed Air Engine - Ahmad, Fathul Hazrimy (2019)
Compressed air engine (CAE) is divided into two types. First type is the fabricated CAE for mobile vehicle and the second type is the retrofitting of compressed air into Spark Ignition Engine and most researches are concentrating on the second type. Retrofit CAE researches use a fixed camshaft lobe as in spark ignition engine. This will make the separation angle between inlet valves open and exhaust valve open fixed and between inlet valves close and exhaust valve close fixed. The purpose of this thesis is to design and develop a CAE that uses an independent valve timing and duration setting of inlet and outlet valves of a compressed air engine in order to identify the best valve timing and duration. This was done by controlling the different angles of valve timing for inlet and outlet compressed air using solenoid valves. Compressed air was fed into the CAE with a certain pressure. The brake power was applied slowly by using a Prony Brake. The different configurations settings of pressure, opening and closing angle of inlet and outlet valves were used in order to find the performance of the CAE. The experiments start from TDC for valve inlet opening, and closing at BDC and valve outlet will start at BDC for opening and TDC for closing. The brake power, the engine speed, and efficiency, at the valve angles setting were recorded. The valve angles setting were from 10° ATDC to 25° ATDC for inlet valve and 140° ATDC to BCD, for outlet valve with an interval of 5° interval. The experiment used a combination of these valve setting were performed 3 times at every setting. This CAE research on variable valve angle setting makes the methodology applicable for studying different angle setting for inlet and outlet of compressed air in the CAE. The best result achieved were at 10° ATDC for inlet opening and outlet closing and 170° ATDC for inlet closing and outlet opening which have an efficiency of 24.58 %. The pressures setting for this experiment were from 1 bar to 3 bar with an interval of 0.5 bar.